Factors Which Influence Incident Hypertension on Pre-Elderly - Siregar, Rahmah Juliani; Rya Anastasya Siregar (PT Inovasi Pratama Internasional, 2022)
The type of research used is an analytic study with cross sectional design. The population in this study were all pre- hypertension suffering as many as 55 people. The sample is the entire population number used as the sample that is as much as 55 people. Data were obtained from Angkola Muaratais Health Center and through interview results using a questionnaire. The results showed statistical test results of independent variables eating habits obtained means there is a significant influence of independent variables with the dependent variable. Physical activity obtained Sig value means there is a significant influence independent variables with dependent. Smoking habits obtained means there is a significant influence independent variables with dependent. Gender obtained indigo means there is no significant influence of independent variable with dependent. Variables that affect the incidence of hypertension. Based on the results of the study concluded there is a lifestyle influence on the incidence of hypertension in the elderly and expected the patient is able to maintain a healthy lifestyle so US to further improve the health status.